2017
DOI: 10.1093/eurheartj/ehx042
|View full text |Cite
|
Sign up to set email alerts
|

Duration of device-detected subclinical atrial fibrillation and occurrence of stroke in ASSERT

Abstract: SCAF >24 h is associated with an increased risk of ischemic stroke or systemic embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
321
1
18

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(353 citation statements)
references
References 30 publications
13
321
1
18
Order By: Relevance
“…Recent data suggests an excess stroke risk in patients with more than 24 hours of continuous AF even when controlling for other stroke risk factors. (34) We would recommend utilising clinical judgement to balance the risk of the risk of bleeding with initiation of systemic anticoagulation with the thromboembolism based on higher AF burden and presence of additional risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggests an excess stroke risk in patients with more than 24 hours of continuous AF even when controlling for other stroke risk factors. (34) We would recommend utilising clinical judgement to balance the risk of the risk of bleeding with initiation of systemic anticoagulation with the thromboembolism based on higher AF burden and presence of additional risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…(7) Similarly, a recently published reanalysis of ASSERT data found that, even when controlling for other stroke risk factors (age, sex, BMI, heart failure, prior stroke, diabetes and arterial disease) a continuous AF burden of more than 24 hours was associated with increased risk of stroke or systemic embolism (hazard ratio 3.24, p=0.003) with no significant difference when comparing shorter durations to no AF. (34) Higher AF burden appears to be associated with higher risk of stroke, at least in part due to the finding that longer duration AHREs have a higher positive predictive for true AF. (28) Risk stratification using clinical risk prediction scores for patients with device-detected AF has been studied.…”
Section: Risk Stratification In Patients With Device-detected Atrialmentioning
confidence: 99%
“…The threshold for a significant increase of TE risk varied from 5 minutes to 24 hours. [17][18][19][44][45][46][47] It seems reasonable to speculate that the implications of AF burden may be different in patients with different baseline risks, in particular in patients with or without prior stroke. An interesting observation supporting the hypothesis of a multivariable model and the absence of a fixed threshold predictive of increased risk is suggested from a proof-of-concept study in which the risk of stroke or TE events was found to be not only a function of the time spent in AF, but also of the baseline characteristics of the patients.…”
Section: Af Burden and Risk Of Strokementioning
confidence: 99%
“…Botto and colleagues, 8 using the groups: no subclinical AF (no AF or AF<6 min), AF of 6 min to 6 h, AF of 6-24 h and AF >24 h. 9 The stroke rates in the first three groups were not significantly different, with hazard ratios of 1, 0.93 and 1.39, respectively, whereas the AF >24 h group had a hazard ratio of 3.86 compared with the no subclinical AF group. Likewise, Boriani and Pettorelli reported that although a device-detected maximum daily burden of AF of at least 5-6 min was associated with an increase in the risk of stroke, the risk was particularly increased if the daily AFB was at least 1 h. 10 Consistent with the above, using 14-day continuous ambulatory recordings to document AF of at least 30 s, Go et al demonstrated that during follow up the rate of validated thromboembolic events off anticoagulants was 2.52/100 patient-years, with a higher crude rate with greater AF burden.…”
Section: Af Burdenmentioning
confidence: 99%